2014
DOI: 10.1161/circep.114.001569
|View full text |Cite
|
Sign up to set email alerts
|

Time Dependence of Risks and Benefits in Pediatric Primary Prevention Implantable Cardioverter-Defibrillator Therapy

Abstract: Background-Implantable cardioverter defibrillators (ICDs) used to prevent sudden cardiac arrest in children not only provide appropriate therapy in 25% of patients but also result in a significant incidence of inappropriate shocks and other device complications. ICDs placed for secondary prevention have higher rates of appropriate therapy than those placed for primary prevention. Pediatric patients with primary prevention ICDs were studied to determine time-dependent incidence of appropriate use and adverse ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 21 publications
0
42
0
2
Order By: Relevance
“…Most studies on ICD complications in pediatric and CHD patients assess all complications and typically highlight inappropriate shocks or other complications such as infection . A recent study shows that 26% of pediatric patients with primary prevention ICDs required reintervention but did not elaborate on indication or timing . System revision is a major complication of ICD implantation, as it requires a surgical procedure which imposes morbidity and increases the risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on ICD complications in pediatric and CHD patients assess all complications and typically highlight inappropriate shocks or other complications such as infection . A recent study shows that 26% of pediatric patients with primary prevention ICDs required reintervention but did not elaborate on indication or timing . System revision is a major complication of ICD implantation, as it requires a surgical procedure which imposes morbidity and increases the risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the life‐saving potential of ICDs, they may impose significant morbidity. Device complications occur in up to 32% of pediatric and congenital heart disease (CHD) patients . A recent study of primary prevention ICDs in this population showed that the risk of complication was greater than the risk of receiving an appropriate shock …”
Section: Introductionmentioning
confidence: 99%
“…From the point of view of risk of ICD, children clearly have a relatively high rate of complications associated with devices, including frequency of inappropriate shocks, lead malfunctions and difficulties in ICD placement related to intracardiac anatomy and small size. 152, 153 Conversely, from the point of view of potential benefits associated with primary prophylaxis, children may stand to gain relatively less from ICD implantation. In particular, the known rate of sudden death associated with congenital heart disease and a variety of arrhythmic cardiomyopathies is considerably lower than that observed in adult populations in whom ICD is seen to be useful (e.g., as mentioned above for adults tetralogy of Fallot, in whom these rates range from 0.1 – 0.2%/yr).…”
Section: Prophylaxis and Secondary Therapy Of Scd In The Youngmentioning
confidence: 99%
“…The rate of inappropriate shocks from all devices in our study was 4.1 per 100 device-years, within the range previously reported for children and patients with CHD: 3.5-9.8 per 100 device years. [1][2][3][4]24 When isolating the new generation devices, however, the incidence of inappropriate shocks was much lower: 6.3% over 4 years follow-up, or 1.3 per 100 device-years.…”
Section: Discussionmentioning
confidence: 99%